Development and Environment in Urmia Lake of Iran - Ghalibaf, Mohammad Bagher; Moussavi, Zahra (European Journal of Sustainable Development, 2014)
Since the end of the Second World War, the development paradigm has become the dominant discourse in the world. During the more than 6 decades that the concept of development discourse has been dominant, many theoretical and practical developments have accompanied it. At first, attention was solely centered on economic development and nature was considered as a facilitator of economic growth. However, it was gradually recognized that development with this economic growth approach changes the natural systems of the planet and leads to numerous environmental hazards that can threaten the economic and political systems of countries. Therefore, it is very possible for a political entity to attain development, but sustained development will be faced with serious doubts because environmental aspects are ignored. Therefore, the concept of sustainable development replaced development. Given the above- mentioned approach, this descriptive-analytic research studied the relationship between economic development and the environment, with Urmia Lake as a case example. Findings of the research show that implementation of Development Plans has been one of the main reasons for the drying up of the Lake. Key Words: Sustainable Development, Environment, Urmia Lake.